A contribuição do design estratégico para a estruturação de uma área de gestão da inovação - Bicca, Evelin Allet (Universidade do Vale do Rio dos Sinos, 2014)
The strategic design and innovation management in a cross-disciplinary perspective have contributed to the construction of new paradigms for the business administration area. This study brings as a problematic, the strategic design as a structuring agent in the area of innovation management in a large company of elevator industry. The exploratory study, consists of making a diagnosis and employing methodologies of strategic design and business management area. In the approach of these methodologies, was tried contribute to the foundations of strategic design in what pertains to research to innovation. As a result, there was a positive and relevant contribution of the strategic design and the method employed, not only in structuring the management innovation sector, but also the introduction of a design culture within the company.
Keywords: Design estratégico; Gestão; Inovação; Strategic design; Innovation; Management